Project “Strengthening the Resilience of Coastal Communities in the North-East Atlantic and Mediterranean Region to the Impact of Tsunamis and Other Sea Level-Related Coastal Hazard” - Intergovernmental Oceanographic Commission; Ryabinin, Vladimir (16 September 2021, 2021)
(IOC/VR/DCS/jao)